Proposta de metodologias de previsão de recalques de grupos de estacas utilizando funções de transferência de carga - Gomes Filho, Francisco Vladson Cardins (2020)
When designing a foundation project, it is necessary to ensure that the elements meet both the ultimate limit state (ELU) and the service limit state (ELS). For this, forecasts of settlement and load capacity are necessary. The methods cargo transfers are a widely used alternative for estimating cargo load-repression ratio of piles, being used, for example, in software that assist in the preparation of foundation projects. However, transfer methods traditional load systems do not take into account the interactive effects between piles in group. Therefore, the present work proposes changes in the transfer curves of load developed by Bohn et al. (2016) so that the group effect is incorporated in the analysis of the load-settlement relationship of groups of piles. Three studies of case, making comparisons with experimental results obtained through carrying out load tests and with determinations made by other authors. In In general, it is concluded that the proposed changes were in agreement with the experimental results of load-settlement relationships for most groups analyzed.